Creativity and Innovation in the Music Industry - Tschmuck, Peter; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Why did jazz become a dominant popular music genre in the 1920s and rock 'n' roll in the 1950s? Why did heavy metal, punk rock and hiphop find their way from sub-cultures to the established music industry? What are the effects of new communication technologies and the Internet on the creation of music in the early 21st century? These and other questions are answered by Peter Tschmuck through an integrated model of creativity and innovation that is based on an international history of music industry since Thomas A. Edison invented the phonograph in 1877. Thus, the history of the music industry is described in full detail. By discussing the historic process of music production, distribution and reception the author highlights several revolutions in the music industry that were caused by the inference of aesthetic, technological, legal, economic, social and political processes of change. On the basis of an integrated model of creativity and innovation, an explanation is given on how the processes and structures of the present music industry will be altered by the Internet, music online services and MP3-technology. A clear indication of a digital revolution in the music industry!
The Emergence of the Phonographic Industry within the Music Industry -- The Music Industry Boom until 1920 -- New Technology and the Emergence of Jazz -- The Music Industry as Radio Industry -- The Swing Monopoly during the Years of Wartime Economy -- Rock 'N' Roll Revolution -- The Recovery of the Phonographic Industry and New Global Players -- The Era of Music Conglomerates -- The Digital Revolution and the Internet -- Theoretical Concepts of Innovation and Creativity -- Creativity and Innovation in the Music Industry -- Creativity and Innovation in the Music Industry's Value-Added Chain.
Keywords: ECONOMICS; ELECTRONIC COMMERCE; HISTORY; MUSIC; INDUSTRIAL ORGANIZATION (ECONOMIC THEORY).; ECONOMICS/MANAGEMENT SCIENCE; INDUSTRIAL ORGANIZATION; MUSIC; R & D/TECHNOLOGY POLICY; HISTORY; ELECTRONIC COMMERCE/E-BUSINESS.